Causes of cost overruns on Zimbabwe’s construction infrastructure projects - Tirivavi Moyo; Benviolent Chigara (Journal of Construction Project Management and Innovation)
The cost performance of infrastructural projects has been problematic, especially in countries with fragile economies like Zimbabwe. However, interrogations of the causes of such cost overruns are scarce within the study area. This article reports on a study that sought to determine the causes of cost overruns on infrastructural construction projects and to establish statistically significant differences in ranking due to quantity surveyor designations. A survey on quantity surveyors from construction companies and quantity surveying consultancy firms in Zimbabwe was instituted and analysed through descriptive and inferential statistics. The most critical causes of cost overruns included currency exchange rate unpredictability, poor financial planning for the project, and an unstable economic climate. A statistically significant difference due to the designations was revealed in individual causes, indicating functional differentiation in determining preventative strategies. Ten components were revealed through factor analysis: excessive use of prime cost and provisional sums, unstable economic fundamentals, project complexity, and duration risks, amongst others. Inculcation of project management competencies, which include risk management, is recommended to resolve these challenges within the Zimbabwean construction industry. There is a need to innovate toward adequate planning for unstable economic climates and risk management. Only the perspectives of quantity surveyors were considered due to the exploratory nature of the study; however, their role in the cost and financial management of construction projects validated their participation in the study.